Anti-Müllerian hormone as a marker of steroid and gonadotropin action in the testis of children and adolescents with disorders of the gonadal axis. (December 2016) - Edelsztein, Nadia; Grinspon, Romina; Schteingart, Helena; Rey, Rodolfo
Abstract In pediatric patients, basal testosterone and gonadotropin levels may be uninformative in the assessment of testicular function. Measurement of serum anti-Müllerian hormone (AMH) has become increasingly widespread since it provides information about the activity of the male gonad without the need for dynamic tests, and also reflects the action of FSH and androgens within the testis. AMH is secreted in high amounts by Sertoli cells from fetal life until the onset of puberty. Basal AMH expression is not dependent on gonadotropins or sex steroids; however, FSH further increases and testosterone inhibits AMH production. During puberty, testosterone induces Sertoli cell maturation, and prevails over FSH on AMH regulation. Therefore, AMH production decreases. Serum AMH is undetectable in patients with congenital or acquired anorchidism, or with complete gonadal dysgenesis. Low circulating levels of AMH may reflect primary testicular dysfunction, e.g. in certain patients with cryptorchidism, monorchidism, partial gonadal dysgenesis, or central hypogonadism. AMH is low in boys with precocious puberty, but it increases to prepubertal levels after successful treatment. Conversely, serum AMH remains at high, prepubertal levels in boys with constitutional delay of puberty. Serum AMH measurements are useful, together with testosterone determination, in the diagnosis of patients with ambiguous genitalia: both are low in patients with gonadal dysgenesis, including ovotesticular disorders of sex development, testosterone is low but AMH is in the normal male range or higher in patients with disorders of androgen synthesis, and both hormones are normal or high in patients with androgen insensitivity. Finally, elevation of serum AMH above normal male prepubertal levels may be indicative of rare cases of sex-cord stromal tumors or Sertoli cell-limited disturbance in the McCune Albright syndrome.